2017
DOI: 10.4103/jisppd.jisppd_15_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hypoxia, sedation level, and adverse events occurring during inhalation sedation using preadjusted mix of 30% nitrous oxide + 70%oxygen

Abstract: None of the children from both groups exhibited hypoxia. Sense of detachment was seen in one child each from both groups. Rapid induction by preadjusted mix resulted in ideal sedation in 57% children of the Group-I; rest had achieved these levels at 40% N2O. There was a significant difference in the time taken to achieve ideal sedation by rapid induction which was almost half the time taken with slow induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The American Academy of Pediatric Dentistry (AAPD) guideline 22 recommends only light meal or clear liquids 2 hours prior to the appointment. 23 , 24 The same was observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The American Academy of Pediatric Dentistry (AAPD) guideline 22 recommends only light meal or clear liquids 2 hours prior to the appointment. 23 , 24 The same was observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Slow induction or titration is a method of administering a drug in incremental amounts until a desired end point is reached, and this method was used to deliver N 2 O to the participants in this study. Samir et al 23 reported that rapid induction of a preadjusted mix of 30% N 2 O and 70% O 2 has the same efficacy as slow induction in achieving optimal sedation in lesser time. However, the titration technique is regarded as the current standard of care when administering N 2 O–O 2 for sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Hand searches of the bibliographies of full-text articles identified 28 additional articles. After full-text evaluation, 19 RCTs [ 13 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 ] published between May 1988 and August 2019 were finally selected for the review. The study screening, selection process, and reasons for exclusion are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In one study [ 40 ], both the intervention and control groups received NOIS but they were administered the mixture using two different techniques. The two groups had a success rate of 100%.…”
Section: Resultsmentioning
confidence: 99%
“…N 2 O is a nonirritating, colorless, inert gas with a faint sweet smell and odor. It is an effective analgesic/anxiolytic agent which causes central nervous system depression and euphoria with little effect on the respiratory system [10,11] . N 2 O-O 2 inhalation sedation is one of the most common pharmacological means of behavioral modification advocated in children and anxious adults owing to its unique properties such as high efficiency, potency, fast onset, rapid recovery, and least adverse effects [8] .…”
Section: Discussionmentioning
confidence: 99%